2015
DOI: 10.1093/infdis/jiv493
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Vaccination Teams During Polio Campaigns in Northern Nigeria by Use of Geographic Information System Technology: 2013–2015

Abstract: Introduction. Nigeria is among the 3 countries in which polio remains endemic. The country made significant efforts to reduce polio transmission but remains challenged by poor-quality campaigns and poor team performance in some areas. This article demonstrates the application of geographic information system technology to track vaccination teams to monitor settlement coverage, reduce the number of missed settlements, and improve team performance.Methods. In each local government area where tracking was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…These data and technology can be used to improve the validity and quality of catchment area maps and population estimates and increase transparency around how such data are generated and used to improve accountability for RI resource allocation. The Global Polio Eradication Initiative (GPEI) has applied geographical information systems (GIS) in Nigeria to track polio vaccination, provide near real-time monitoring of team performance and identify service gaps since 2012 8 12–14. In 2017, the Bauchi and Sokoto SPHCDAs, with support from the Maternal and Child Survival Program (MCSP) of the US Agency for International Development, sought an alternative approach to improve RI microplanning using GIS technology.…”
Section: Context and Approachmentioning
confidence: 99%
“…These data and technology can be used to improve the validity and quality of catchment area maps and population estimates and increase transparency around how such data are generated and used to improve accountability for RI resource allocation. The Global Polio Eradication Initiative (GPEI) has applied geographical information systems (GIS) in Nigeria to track polio vaccination, provide near real-time monitoring of team performance and identify service gaps since 2012 8 12–14. In 2017, the Bauchi and Sokoto SPHCDAs, with support from the Maternal and Child Survival Program (MCSP) of the US Agency for International Development, sought an alternative approach to improve RI microplanning using GIS technology.…”
Section: Context and Approachmentioning
confidence: 99%
“…The app enables them to discuss new cases quickly and to determine where VCMs should be located. This partner funded information system should play a crucial role in the future, she says 1…”
Section: End Of the Roadmentioning
confidence: 99%
“…Five studies that involved polio, cholera, and measles campaigns applied mHealth to improve the organization and planning for mass vaccine campaigns (Table 3). Electronic data collection for pre-campaign surveys helped identify areas that were missed by previous campaigns and establish a strategy for isolated communities [22,23,24,25,26]. In one study from Haiti, geospatial mapping of campaign activity proved to be a useful tool for campaign strategy planning [23].…”
Section: Campaign Strategic Planningmentioning
confidence: 99%
“…Studies have identified a growing capacity for health workers in developing countries to adapt and use smartphones for health related interventions as well as a variable willingness to abandon their old system to a new one [6,11]. However, unreliable or spotty networks may be a barrier in remote settings [21,22,23,24,25]. Some of the examples where connectivity issues impeded vaccine activity efforts include settings where more than one-half of households at a site did not have GPS coordinates for geospatial mapping and campaign planning.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation